Legislation on direct democracy in modern Vietnam - T. T. Thoa (Управление)
In recent years, direct democracy has received more and more attention and has become the subject of much research in the field of political science. The development of direct democracy is seen as a mean of consolidating modern democracy. Therefore, most democratic countries in the world have been making efforts to build appropriate mechanisms to promote the positive effects of this form of democracy, including Vietnam. Characterized as a developing country with a single-party ruling political system, Vietnam aims to build a united and cohesive society on the basis of ensuring the people’s mastery through direct and representative democracy. Since entering the period of renovation (since 1986), direct democracy has been of more interest in Vietnam along with the legal basis system for this form of democracy is increasingly improved. However, it must be acknowledged that, for a country that has not had a long history of implementing democracy, especially direct democracy, the Vietnamese legal system that regulates this field still has many limitations. The article gives an overview of the current legal system of direct democracy in Vietnam, thereby analyzing a number of limitations and shortcomings and orienting some solutions to overcome these problems.